Analisis Pengaruh Perkembangan Inovasi Pangan Pada Tingkat Konsumsi Masyarakat di Jawa Barat - Putri, Deswita Kartika; Awaluddin, Mochamad Reza; Ramadhani, Risma (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The aim of this research is to analyze and describe the forms of expressive speech acts produced by children playing in the H. Saemin area, Pondok Pinang. The method used is the observe-note-classify-analyze method with data collection techniques through observation. From the research results, conversation data was obtained for 7 illocutionary speech acts in the category of expressive speech acts. Through 7 conversation data from children with the initials RKY (K), RZA (Z), ADN (D), and AZM (A), 15 expressive utterances were obtained in the data game, including expressions of greeting, insulting, blaming, thanking. love, complain, praise, apologize and criticiz Food products can be defined as processing or production results obtained from food ingredients. The diversity of local food products in Indonesia opens up great potential for food innovation. Utilizing local food products can be done by creating processed creations that suit people's interests, which can change their eating habits and lifestyle, both positively and negatively. Food innovation often introduces new variations in food choices, which can enrich people's diets. With food innovation, there can be changes in people's food consumption and innovation can affect people's health as a whole. Innovations that focus on increasing the nutritional content of food can improve public health. This research aims to provide support for local products, and increase the level of public consumption of food innovation. This research method uses a questionnaire as a tool for conducting quantitative research. The questionnaire consists of five questions with a rating scale of 1 to 5 which explore respondents' interest in food innovation in society, especially in West Java. Based on the results of the questionnaire data obtained, the majority of respondents stated that they quite often consume food innovation products because they are interested in them. It can be understood that the existence of food innovations in circulation can influence the level of consumption and people's preferences for food innovations.